Absorption and transport of radiophosphorus as a function of the number of adventitious roots of sugar cane setts - Arevalo, Roberto A.; Malavolta, Eurípedes; Camargo, Paulo N. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1984)
Sugar cane setts with a variable number of roots (1, 2, 4 and 8) were allowed to absorb radiophosphate. Afterwards the material was split into several parts and its radioactivity was counted. It was observed that both absorption and transport increased with the number of roots.